Matrix Metalloproteinases and their Inhibitors in Vascular Remodeling and Vascular Disease - Raffetto, Joseph D. (2007)
Matrix metalloproteinases (MMPs) are a family of proteolytic enzymes that degrade various components of the extracellular matrix (ECM). Members of the MMP family include collagenases, gelatinases, stromelysins, matrilysins and membrane-type MMPs. ProMMPs are cleaved into active forms that promote degradation of ECM proteins. Also, recent evidence suggests direct or indirect effects of MMPs on ion channels in the endothelium and vascular smooth muscle, and on other mechanisms of vascular relaxation/contraction. Endogenous tissue inhibitors of metalloproteinases (TIMPs) reduce excessive proteolytic ECM degradation by MMPs. The balance between MMPs and TIMPs plays a major role in vascular remodeling, angiogenesis, and the uterine and systemic vasodilation during normal pregnancy. An imbalance in the MMPs/TIMPs activity ratio may underlie the pathogenesis of vascular diseases such as abdominal aortic aneurysm, varicose veins, hypertension and preeclampsia. Downregulation of MMPs using genetic manipulations of endogenous TIMPs, or synthetic pharmacological inhibitors such as BB-94 (Batimastat) and doxycycline, and Ro-28-2653, a more specific inhibitor of gelatinases and membrane type 1-MMP, could be beneficial in reducing the MMP-mediated vascular dysfunction and the progressive vessel wall damage associated with vascular disease.